Numerical modeling of the tension-compression behavior of tie connections in brick masonry walls - Ortega Heras, Javier (2022)
Brick masonry veneer walls connected to infill walls inserted in a reinforced concrete (RC) frame is a very common constructive system in Portugal. The stability of the veneer wall is ensured by ties that make the connection with the masonry infill walls. These ties are the main structural element transferring the out-of-plane loads to the main structure during an earthquake. However, the characterization of the seismic behavior of these tie connections is an insufficiently explored topic. The present paper shows a numerical investigation that aims to simulate experimental results of tension and compression tests performed on masonry wallets connected by means of steel ties. The main objective of the present research is to obtain a better understanding of the complex structural behavior of this specific construction system to eventually develop simplified numerical tools to be used in engineering practice for the seismic design and retrofitting of brick masonry veneer walls.